Legal Education and Upbringing of Order - Musaraj, Joniada (European Journal of Multidisciplinary Studies, 2021)
A great importance to a democratic society is the creation of legal literacy education on rule. Such a breeding seems to be primarily present in the consciousness of every citizen. The principles of a democratic state should be installed, first to society. These principles embodied in the individual consciousness in the form of legal and institutional consciousness. Moreover every man should know that c `demands of an institution, and should make it impossible to solve the institutional and democratic way, even when he finds the office door closed, even by officials when a problem exists as insoluble. An individual should not be equated with the passivity that is generally characterized by officials, but must use every means to protect the right and dignity. Methodology: First, quantitative analysis was used to see why the number of citizens dissatisfied with the exercise of their rights is increasing. Secondly, qualitative analysis was used by analyzing the social and objective causes that lead to a lack of legal education of the public. Expected results: the consequent link between the lack of information on the law and non-exercise of the right. This scientific paper seeks to give concretely what are some of the strategies that should be used to have a well-informed public and satisfied with the exercise of law.